Synthesis, Characterization, and Application of Magnetite Nanoparticles Coated with Hydrophobic Polyethyleneimine for Oil Spill Cleaning - Abdelrahman O. Ezzat; Mohd Sajid Ali; Hamad A. Al-Lohedan (Journal of Chemistry, 2022)
Pollution with oil spills, a major contributor to water contamination, has a remarkable effect on the economy, biodiversity, and environment. To protect marine species and environment, efforts should be undertaken for developing efficient ways to remove oil spills. The current work discusses the oil spill removal using magnetite nanoparticles (MNPs) functionalized with hydrophobic polyethyleneimine (HPEA). In this respect, nonylphenol pentaethylenehexamine (NTEPA) and nonylphenol triethylenetetramine (NDETA) were prepared by a simple one-step method and used as capping agents in the synthesis of hydrophobically modified magnetite nanoparticles designated as NDETA/Fe3O4 (magnetite as a core and NDETA as a shell) and NTEPA/Fe3O4 (magnetite as a core and NTEPA as a shell). The prepared MNPs were characterized using FTIR, XRD, TEM, DLS, TGA, and DSA to determine their physical and chemical properties. Additionally, MNPs were applied as oil spill collectors with high efficiencies that reached 93% and 90% for NDETA/Fe3O4 and NTEPA/Fe3O4, respectively, at low magnetite to oil ratios.